2016
DOI: 10.1111/clr.12930
|View full text |Cite
|
Sign up to set email alerts
|

Deviations of different systems for guided implant surgery

Abstract: The clinician may have considerable impact on the accuracy of GIS when applying eccentric forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 12 publications
(19 reference statements)
1
43
1
Order By: Relevance
“…In our setting, this friction was reduced to a minimum by the drills being positioned in the center of each handle. Under clinical conditions, generally speaking a loose fit between drill and sleeve potentially causes eccentric forces, which lead to more friction and greater heat development (Laederach, Mukaddam, Payer, Filippi, & Kühl, ). A greater temperature difference between guided and conventional drilling procedures was observed in the current study for large diameter drills and larger drill flutes because of the influence of water irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our setting, this friction was reduced to a minimum by the drills being positioned in the center of each handle. Under clinical conditions, generally speaking a loose fit between drill and sleeve potentially causes eccentric forces, which lead to more friction and greater heat development (Laederach, Mukaddam, Payer, Filippi, & Kühl, ). A greater temperature difference between guided and conventional drilling procedures was observed in the current study for large diameter drills and larger drill flutes because of the influence of water irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic radiographic fidelity of bone structures and accuracy of linear measurements are crucial for basic preoperative implant planning, and even more so when applied in image‐guided implant surgery (Nickenig & Eitner, ; Schneider, Marquardt, Zwahlen & Jung, ; Vieira, Sotto‐Maior, Barros, Reis & Francischone, ). All guided surgery systems incorporate some degree of imprecision resulting in horizontal and particularly vertical deviations of the actual position of the implant compared to the presurgical virtual position (Laederach, Mukaddam, Payer, Filippi & Kuhl, ; Schneider et al., ; Vercruyssen et al., , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the few large deviations is the technical skills of the surgeon. In an in vitro study, Laederach et al [27] concluded that the clinician might have considerable influence on the accuracy of sGIS when applying eccentric forces. Considering the simulation was executed in a well-controlled environment, the few large deviations could be attributed to the personal technical skills of individual surgeon.…”
Section: Discussionmentioning
confidence: 99%